2021
DOI: 10.4103/jfmpc.jfmpc_747_21
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19–induced anxiety and protective behaviour among nursing students

Abstract: Introduction: The COVID-19 Pandemic has caused anxiety and stress among people. Nursing students, being an important link in the delivery of health care services, are always exposed to stressful situations which in turn put a great toll on their mental health. Moreover, the perceived risk of pandemics motivates people to embrace different protective measures so as to reduce any potential threats of an emerging health concern. Objective: The aim of this study was to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
2
3
0
Order By: Relevance
“…Moreover, the finding of the present study indicated that parent's level of education is a protective factor against anxiety. These results of the present study are in accordance with the findings of the studies conducted by (AlAzzam et al, 2021;Alrubaiee et al2020;Nebhinani et al,2021), they found that parent's level of education was statistically and significantly associated with students' anxiety level association with their, and sex of the students. This may be justified by high level of education might help parents to gaining more scientific knowledge concerning Omicron variant, and protective behavior.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, the finding of the present study indicated that parent's level of education is a protective factor against anxiety. These results of the present study are in accordance with the findings of the studies conducted by (AlAzzam et al, 2021;Alrubaiee et al2020;Nebhinani et al,2021), they found that parent's level of education was statistically and significantly associated with students' anxiety level association with their, and sex of the students. This may be justified by high level of education might help parents to gaining more scientific knowledge concerning Omicron variant, and protective behavior.…”
Section: Discussionsupporting
confidence: 93%
“…The rapid increase in corona cases across the world caused a widespread panic. The accumulated unknowns and uncertainties about COVID-19 cause worry and anxiety, reducing public vigilance and adherence to protective behaviors (Nebhinani et al, 2021). Adolescence is a period in life during which adolescents undergo developmental changes that affect not only their physical health, but also psychological and social health (WHO, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This finding aligns with another study that did not find independent predictors of suicidal ideation and self-harm among participants [49]. However, it contradicts a different study suggesting a statistically significant association between anxiety level and participant age [8]. Age was also found to be a significant predictor of moderate-to-high anxiety among the general public in a study conducted in Canada during the pandemic, with the cohort aged 25 years or younger more likely to experience moderate-to-high anxiety [50].…”
Section: Predictors Of Gad and Mddsupporting
confidence: 85%
“…Anxiety, characterized by a diffuse emotional state anticipating potential harm or uncertain threats, poses a significant health issue for this age group [ 5 , 6 , 7 ]. Notably, a study conducted during the COVID-19 pandemic reported a 75% incidence of moderate anxiety among young adults aged 21 to 25 years, a critical transition stage marked by physiological and psychological changes that may result in loneliness leading to depression as well as low self-esteem [ 8 , 9 ]. Additionally, a global study across 82 countries found anxiety prevalence among adolescents ranging from 7% to 12%, with the highest pooled prevalence of 17.0% [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…An African study conducted among medical students found that 88.8% of participants experienced depression, while 82.6% of participants experienced anxiety [6]. Moreover, higher estimates of anxiety (75.5%) [16] and depression (84.4%) were reported in a cross-sectional survey of medical students [17].…”
Section: Introductionmentioning
confidence: 98%